Salud mental y discriminación por razones de género en el marco del aborto terapéutico en el Perú - Nalvarte Cuzcano, Dessiré (2019)
The article develops a descriptive research approach on a 2015 particular case reported to INDECOPI because a clinic did not evaluate the mental health of a pregnant woman and correctly processed her request for therapeutic abortion, as well as that she would have suffered gender discrimination. Therefore, it is analyzed whether legally, in our country, there is an obligation to evaluate the mental health of the pregnant woman and what should be understood as “serious and permanent health damage”, as it is contemplated in the legal devices. This document also develops gender discrimination in the commercial sphere and how gender stereotypes of the medical personnel led to denying the requested service that merited the medical stage of the pregnant woman.